Electronic Media Marketing Mix Analysis on Increasing Participant of BPJS Ketenagakerjaan - Mandung, Fitriani (Manunggal Halim Jaya, 2022)
This research was conducted to know the effect of each variable in the electronic media mix consisting of television, radio, and Internet media significantly on the increasing participant of BPJS Ketenagakerjaan in the Makassar Branch, as well as to determine the effect simultaneously or simultaneously of electronic media variables on television media, radio media, and internet media to increase BPJS Ketenagakerjaan membership in the Makassar Branch. This study uses questionnaire data, literature studies, and interviews with data analysis techniques of the quality test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The study's results found that electronic media consisting of television, radio, and internet media significantly influenced BPJS Ketenagakerjaan membership in the Makassar Branch, so the first hypothesis can be accepted. Based on the results of simultaneous testing, the F-calculated = 398,637 with a significance < 0.01 with an omission of 0.05, so it can be said that television media, radio media, and internet media together affect increasing Participants of BPJS Ketenagakerjaan in the Makassar Branch so that the second hypothesis proposed can be accepted and proven genuine.